Case studies on forensic structural engineering - Nguee, Ching Seng (2006)
Forensic engineering is the application of engineering science to the investigation of failure or performance problem. This field of engineering has a big potential in Malaysia as more expertise is required to carry out forensic engineering investigation on failed civil infrastructure. This study involves detailed analysis of methodologies for forensic investigation from four case studies representing different types of structural forms and causes of failure. In order to analyse the case studies, the objectives of investigation of each case study had been derived. In addition, detailed analysis of the failure hypothesis, investigation approaches, causes of failure, modes of failure and application of engineering mechanics that explained the failure mechanism for each case study had also been carried out. The case studies have demonstrated that, although some specific aspects in the methodology may differ from one case to another, the basic element of the methodology remain the same for all cases and it also showed how the selection of appropriate testing methods and analytical techniques can help to confirm the finding and verify the failure hypothesis. The result in terms of comparison between case studies with their different unique features, testing techniques, analytical methods and engineering mechanics are presented in this study. Finally, based on the understanding and analyses of the different features of the case studies, a general guideline of methodology of forensic engineering investigation is proposed. This general methodology is applicable to all forensic engineering investigation to implement best practices in the conduct of forensic engineering investigation, but the specific activities will differ depending on the nature of the problem. Based on the general guideline, the investigators will know the general procedure of the investigation activities involved in the forensic structural investigation.